Proses Penerbitan Dokumen Persetujuan Keagenan Kapal Asing (PKKA) pada PT. Pelayaran Dwi Putra Laksana Batam - Erika Situmorang; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Approval of Foreign Ship Agency (PKKA) is a requirement in the form of a letter obtained from the system established by the Ministry of Transportation. This letter is useful when the Shipping Agency tasked with representing foreign ships in Indonesian ports, or appointed by the shipowner to carry out duties. Approval for foreign-flagged vessel agencies serves the PKKA Tramper route to support domestic and international maritime transport. The registration of foreign ships involves adding data or registering ships in Simlala that have never entered or been represented by the respective company due to the absence of the ship's name on the Approval of Foreign Ship Agency (PKKA). If the ship has already entered an Indonesian port through the respective agency, there is no need to register the ship in the Simlala system. Simlala is an innovation from the Indonesian Ministry of Transportation, involving the use of online systems or the internet in ship and port services, with Port Authorities as the implementers, to keep up with the developments in the maritime world, where the speed of port services is crucial. In the Simlala system, shipping companies have accounts registered with the Port Authority, and anyone wishing to access the Simlala system must also have an account used to request ship services. In writing this paper, the author conducted field research, including observation, which is the most dominant method used, as well as interview and library research methods.